2020
DOI: 10.1016/j.physrep.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on conventional high-temperature superconductors at high pressure: Methods and materials

Abstract: Two hydrogen-rich materials: H 3 S and LaH 10 , synthesized at megabar pressures have revolutionized the field of superconductivity by providing a first glimpse into the solution for the hundred-year-old problem of room-temperature superconductivity. The mechanism governing these exceptional superconductors is the conventional electron-phonon coupling. Here, we describe recent advances in experimental techniques, superconductivity theory and first-principles computational methods, which made this discovery pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
364
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(377 citation statements)
references
References 589 publications
(782 reference statements)
10
364
0
3
Order By: Relevance
“…Despite a fact that H3S is widely classified as conventional [7] electron-phonon superconductor [1,[3][4][5][6][8][9][10][11][12][13], we performed [14] analysis of experimental upper critical field data, Bc2(T), reported by Mozaffari et al [15,16], and showed that H3S is unconventional superconductor which lies in common unconventional superconductors trend band of the Uemura plot [17,18] together with other unconventional superconductors, i.e. heavy fermions, fullerenes, pnictides, and cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a fact that H3S is widely classified as conventional [7] electron-phonon superconductor [1,[3][4][5][6][8][9][10][11][12][13], we performed [14] analysis of experimental upper critical field data, Bc2(T), reported by Mozaffari et al [15,16], and showed that H3S is unconventional superconductor which lies in common unconventional superconductors trend band of the Uemura plot [17,18] together with other unconventional superconductors, i.e. heavy fermions, fullerenes, pnictides, and cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach was not widely adopted until Ashcroft's suggestion [2] that high-pressure conditions can metallize hydrogen-rich materials that are insulators at ambient pressure. Subsequently, there has been much research on hydrogen-rich hydrides under high pressures [3][4][5][6]. Breakthroughs were achieved in SH 3 and LaH 10 systems, which had high T c of ∼200 and 250-260 K, respectively [7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Mass isotope data for DH 10 reported in [12], deemed inconclusive in [4], are shown to more likely reflect the inverse correlation between T C and the fractional transition width T C /T C , as is found for D 3 S. Consequently, and notwithstanding the predictions of Éliashberg theory, the precise role played by phonons in the superconductivity of MH n awaits further investigation. Since quantitative scaling with the theoretical e 2 / is noted from optical evidence for compressed A15 Cs 3 C 60 [49] and H 3 S [41], and plausibly extending to LaH 10 , reflectivity measurements of MH n may prove invaluable in determining the nature of the mediating boson.…”
Section: Resultsmentioning
confidence: 86%
“…The LaH 10 clathrate, exhibiting superconductivity at temperatures of about 250 K [12] and above 260 K [13] for applied pressures P ~ 137 -218 GPa, currently holds the record for the highest transition temperature, T C . Electron-phonon interaction theory rooted in strong-coupling Migdal-Éliashberg methodology [17][18][19], density functional theory, or ab initio methods [4,20], predicts T C for LaH 10 spanning a broad range of 199 -288 K [4][5][6][21][22][23][24][25][26] and monotonically decreasing with increasing pressure [5,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation